Levels of Physical Activity Are Associated With the Motivational Climate and Resilience in University Students of Physical Education From Andalucía: An Explanatory Model - Chacón-Cuberos, Ramón; Castro-Sánchez, Manuel; Pérez-Turpin, José Antonio; Olmedo-Moreno, Eva María; Zurita Ortega, Félix (Frontiers in Psychology, 2019)
(1) Background: The practice of Physical Activity (PA) is a key factor for the improvement of physical and mental health, being of interest the study of the motivational processes that operate in the development of active lifestyles; (2) Methods: This cross-sectional study was conducted on 775 university students of Physical Education from Spain. This research aims to develop an explanatory model for the relationships between motivational climate and resilience capacity according to the level of PA, using structural equations analysis. The main instrument used were the Perceived Motivational Climate in Sport (PMCSQ-2) and the Connor-Davidson Resilience Scale (CD-RISC); (3) Results: A negative relationship was observed between task-oriented climate and ego-oriented climate, which acquired greater correlation strength in the respondents who did less PA. Likewise, a positive relationship was obtained between task-oriented climate and resilience, which was higher in participants who performed more than three hours of weekly PA. Finally, it was observed that resilience was highly correlated with personal competence, tenacity and control capacity in the most active subjects; (4) Conclusions: It is highlighted the interest of promoting task-oriented motivational climates in PA and sport, since this will develop a greater resilience capacity in university students, and will favour the tolerance to adversity and the positive acceptance of changes.